(untitled) (Journal of Universal Science Research, 2025)
The rapid development of Artificial Intelligence (AI) and Natural Language Processing (NLP) has significantly influenced human language use. Among the most prominent AI tools, ChatGPT has become a major agent in shaping and expanding the English lexicon while providing innovative opportunities for language learning. This paper examines how AI-specifically ChatGPT – has contributed to lexical innovation, changed language practices, and served as a dynamic educational tool. Through a mixed-methods approach, this study investigates the emergence of neologisms, shifting semantic fields, and the incorporation of AI in language pedagogy. The findings indicate that AI technologies are not only reshaping English vocabulary but also enabling more personalized and effective language acquisition strategies.